Chronic inflammatory liver diseases and coffee intake. Issue 5 (September 2019) - Contaldo, Franco; Santarpia, Lidia; Pasanisi, Fabrizio
Abstract : Purpose of review: To review the healthy protective effects of coffee against several metabolic diseases and some types of cancer. In this short review, the possible preventive and/or therapeutic actions of coffee on liver function is focused. Recent findings: The protective mechanisms of coffee are various and because of several components with anti-inflammatory and antioxidant properties in addition to caffeine. As a matter of the fact, polyphenols in decaffeinated coffee have a similar effect on liver fibrosis and on serum levels of liver enzymes as those in caffeinated coffee. Furthermore, diterpenes may exert a detoxifying action and antioxidant activity, with benefits on liver fibrosis, cirrhosis and cancer. Summary: A regular coffee consumption may have preventive healthy effects, especially if consumed without added sugars. Certainly, coffee consumption should not be prohibited in individuals with chronic inflammatory liver diseases, including hepatocellular carcinoma.